2015
DOI: 10.1016/j.ijgo.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury rates among primiparous women with different modes of vaginal delivery

Abstract: Phone+61 2 9462 9814 Fax +61 2 9906 6742 Keywords:Obstetric anal sphincter injury; record linkage study; forceps; vacuum; international classification of diseases Synopsis (25 words)Non-instrumental births without episiotomy, and forceps with episiotomy, were the only birth modes where the risk of OASI increased significantly over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…The incidence of OASIS remained low during the study period, in contrast to some reports from Australia [ 24 ] and the UK [ 25 ]. The low incidence in Finland might be due to the practice of manually supporting the perineum when the baby’s head is crowning through the vaginal introitus [ 11 ].…”
Section: Discussioncontrasting
confidence: 67%
“…The incidence of OASIS remained low during the study period, in contrast to some reports from Australia [ 24 ] and the UK [ 25 ]. The low incidence in Finland might be due to the practice of manually supporting the perineum when the baby’s head is crowning through the vaginal introitus [ 11 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Changes in demographic risk factors such as the rise in maternal age, higher fetal birthweight, improvement of diagnostic attention, and better documentation through national birth registries explain only part of the substantial increase in obstetric anal sphincter injuries 8. Interestingly, in some countries, the use of forceps at delivery, although one of the major risk factors, has risen in the past years and may have contributed to this trend 8, 10…”
Section: Introductionmentioning
confidence: 99%
“…8 Interestingly, in some countries, the use of forceps at delivery, although one of the major risk factors, has risen in the past years and may have contributed to this trend. 8,10 Using the population-based database from the Austrian national birth registry, the aim of this study was to analyze risk and protective factors for obstetric anal sphincter injuries in first births in Austria and to describe time trends about the incidence of these injuries and associated risk factors in a country with a long-standing tradition of restricted use of forceps at delivery.…”
mentioning
confidence: 99%
“…At 18 months follow‐up, 20 reported mild incontinence and four with moderate incontinence (Tjandra et al ). An observational study by Ampt et al (), indicated that the risk of sphincter injury rates have increased between the years 2001 to 2011 among both women that underwent delivery with the use of an episiotomy and without it. Yet the difference was found in whether the episiotomy was accompanied with any other instrumental aids.…”
Section: Anatomical Dissatisfactionmentioning
confidence: 99%